Long non-coding RNA-dependent mechanism to regulate heme biosynthesis and erythrocyte development. Issue 1 (December 2018) - Liu, Jinhua; Li, Yapu; Tong, Jingyuan; Gao, Jie; Guo, Qing; Zhang, Lingling; Wang, Bingrui; Zhao, Hui; Wang, Hongtao; Jiang, Erlie; Kurita, Ryo; Nakamura, Yukio; et al.
Abstract In addition to serving as a prosthetic group for enzymes and a hemoglobin structural component, heme is a crucial homeostatic regulator of erythroid cell development and function. While lncRNAs modulate diverse physiological and pathological cellular processes, their involvement in heme-dependent mechanisms is largely unexplored. In this study, we elucidated a lncRNA (UCA1)-mediated mechanism that regulates heme metabolism in human erythroid cells. We discovered that UCA1 expression is dynamically regulated during human erythroid maturation, with a maximal expression in proerythroblasts. UCA1 depletion predominantly impairs heme biosynthesis and arrests erythroid differentiation at the proerythroblast stage. Mechanistic analysis revealed that UCA1 physically interacts with the RNA-binding protein PTBP1, and UCA1 functions as an RNA scaffold to recruit PTBP1 toALAS2 mRNA, which stabilizesALAS2 mRNA. These results define a lncRNA-mediated posttranscriptional mechanism that provides a new dimension into how the fundamental heme biosynthetic process is regulated as a determinant of erythrocyte development. LncRNAs modulate diverse physiological cellular processes, however, their involvement in heme-dependent processes are not yet clear. Here the authors reveal the role of lncRNA UCA1 in erythroid cell development.